Disseminated Soft Tissue Infection and Sepsis with Stenotrophomonas maltophilia in a Bone Marrow Transplant Patient - Jeffrey H Lipton; Kelly S MacDonald (Canadian Journal of Infectious Diseases)
A 32-year-old female presented with aplastic anemia and subsequently underwent a one-antigen mismatched bone marrow transplant from her brother. She failed to engraft and a second graft was attempted. Protracted neutropenia of three months’ duration despite the use of broad spectrum antibiotics occurred. Stenotrophomonas (Xanthomonas) maltophilia metastatic cellulitis developed that did not respond to appropriate antibiotics.